Patient position verification in magnetic-resonance imaging only radiotherapy of anal and rectal cancers. (July 2021) - Bird, David; Beasley, Matthew; Nix, Michael G.; Tyyger, Marcus; McCallum, Hazel; Teo, Mark; Gilbert, Alexandra; Casanova, Nathalie; Cooper, Rachel; Buckley, David L.; Sebag-Montefiore, David; Speight, Richard; et al.
Highlights: MR-only patient positioning for anal and rectal cancers using CBCT. MR-only results in systematic positioning differences to of <±1 mm and <±0.5°. Vendors need to clinically enable alternative modalities as reference images. Abstract: Background and Purpose: Magnetic resonance (MR)-only treatment pathways require either the MR-simulation or synthetic-computed tomography (sCT) as an alternative reference image for cone beam computed tomography (CBCT) patient position verification. This study assessed whether using T2 MR or sCT as CBCT reference images introduces systematic registration errors as compared to CT for anal and rectal cancers. Materials and Methods: A total of 32 patients (18 rectum, 14 anus) received pre-treatment CT- and T2 MR- simulation. Routine treatment CBCTs were acquired. sCTs were generated using a validated research model. The local clinical registration protocol, using a grey-scale registration algorithm, was performed for 216 CBCTs using CT, MR and sCT as the reference image. Linear mixed effects modelling identified systematic differences between modalities. Results: Systematic translation and rotation differences to CT for MR were −0.3 to + 0.3 mm and −0.1 to 0.4° for anal cancers and −0.4 to 0.0 mm and 0.0 to 0.1° for rectal cancers, and for sCT were −0.4 to + 0.8 mm, −0.1 to 0.2° for anal cancers and −0.6 to + 0.2 mm, −0.1 to + 0.1° for rectal cancers. Conclusions: T2 MR or sCT can successfully be used as reference images for anal and rectal cancer CBCT position verification with systematic differences to CT <±1 mm and <±0.5°. Clinical enabling of alternative modalities as reference images by vendors is required to reduce challenges associated with their use.